2020
DOI: 10.1002/lt.25669
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Is Associated With Increased Rates of Acute Cellular Rejection Within 3 Months After Liver Transplantation

Abstract: Frailty, a state of decreased physiological reserve, has been associated with dysregulation of the immune system. We hypothesized that frailty is associated with differential rates of acute cellular rejection (ACR) in liver transplantation (LT) recipients. Our study included LT recipients from 2014 to 2016 who had a pre‐LT frailty assessment using the liver frailty index (LFI). Frailty was defined as an LFI ≥4.5. ACR at 3 months was ascertained from pathology reports, and immunosuppression regimens were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…This is consistent with what we previously observed in liver transplant recipients, in whom frailty was associated with increased rates of acute cellular rejection. 30 Potential mechanisms for these higher rejection rates imply that frail patients have an increased inflammatory state 31 and tend to experience higher rates of mycophenolate dose reduction than nonfrail recipients. 30 In other words, one could hypothesize that low PMI patients receive less immunosuppression because the management team is more prone to reduce doses to avoid overimmunosuppression-related complications in these frail patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with what we previously observed in liver transplant recipients, in whom frailty was associated with increased rates of acute cellular rejection. 30 Potential mechanisms for these higher rejection rates imply that frail patients have an increased inflammatory state 31 and tend to experience higher rates of mycophenolate dose reduction than nonfrail recipients. 30 In other words, one could hypothesize that low PMI patients receive less immunosuppression because the management team is more prone to reduce doses to avoid overimmunosuppression-related complications in these frail patients.…”
Section: Discussionmentioning
confidence: 99%
“…(2)(3)(4)(5) Within this context, Fozouni et al investigated the association of frailty and acute cellular rejection (ACR) in a retrospective, single-center cohort study of 241 liver transplant patients. (6) After controlling for a number of potential confounders using bivariate logistic regression modeling, the authors found frailty was strongly associated with ACR in the 90-day period following transplantation. Most importantly, the authors found the same association after adjusting for changes in immunosuppression dose, which occurs at disproportionately high rates among the frail population.…”
Section: To the Editormentioning
confidence: 99%
“…We read with interest the study performed by Fozouni et al (1) on the association between pretransplant frailty and increased risk of early acute cellular rejection (ACR) after liver transplantation (LT). Chronic systemic inflammation, which is frequently detected in frail patients, was suspected by Fozouni et al as the underlying pathogenic mechanism.…”
Section: To the Editormentioning
confidence: 99%
“…(3) Frailty is a complex syndrome in which aging, sarcopenia, malnutrition, comorbidities, and disability play an integrated pathogenic role. (2) The study performed by Fozouni et al (1) has the value of using the liver frailty index as an assessment method, which surely explores frailty in a comprehensive and integrated way and with no terms of comparison from previous studies.…”
Section: To the Editormentioning
confidence: 99%